Features of migration trends between Kazakhstan and Russia - Naimanbayev, Bekmurat R.; Kairgaliyeva, Gulfairuz; Orynbassarova, Gulzhan Z.; Shavkat Rakhimkulov, Rukhsara Ynussova, (Opción, 2019)
The article analyzes the features of the migration policy of Kazakhstan and Russia at the beginning of the XXI century via comparative qualitative research methods. As a result, emigration to Russia from Kazakhstan is growing at the expense of all representatives of all ethnic groups, the main of which are Kazakhs and Russians. In conclusion, the flows of labor migrants with a vector from Kazakhstan to Russia and from Russia to Kazakhstan will increase in the medium term, especially in connection with the formation of the Eurasian Economic Union.